Subtypes of Bullying and Friends’ Delinquency: Is Religiosity a Moderator? - Hong, Jun Sung (Review of religious research, 2024)
Increasingly, bullying research has focused on identifying protective factors associated with bullying involvement (e.g., victim, perpetrator) and adverse outcomes. In this study, religiosity was examined as a protective factor in the relationship between bullying involvement and friends’ delinquency among a large sample of low-income urban African American adolescents (N = 753). Analysis of the cross-sectional data indicated that bullying perpetration, victimization, and victimization/perpetration were positively associated with greater friends’ delinquency. Further, adolescents who bullied others were less likely to report having friends engaging in delinquency when they reported attending church or other religious services. Also, adolescents who reported both victimization and perpetration of bullying, who placed great importance on religious or spiritual beliefs, were less likely to associate with friends engaging in delinquency. This study demonstrates how religiosity should be considered in bullying prevention and intervention efforts.